Pierre Macherey, From Canguilhem to Foucault: the Force of Norms (In French) - Fulka, Josef (Teorie vědy / Theory of Science, 2010)
Review: Pierre MACHEREY, De Canguilhem à Foucault : La force des normes. Paříž: La Fabrique 2009, 140 s.